Inclusion of people with disabilities through fights and martial arts (Revista de Artes Marciales Asiáticas, 2016)
This article aimed at investigating how the fights / martial arts were adapted for inclusion of people with disabilities in the social sphere as well as for rehabilitation and sports-competition. The analysis was initially made at the global level and later specific attention was paid to the Brazilian reality, through a narrative review of literature. The following fights / martial arts were considered: fencing, judo, karate, kung fu, boxing, taekwondo and capoeira. It was concluded that the fights / martial arts can contribute to combating social exclusion, contributing to the promotion of health, beauty and leisure and new talents in parasports can be discovered too. Further studies on the subject are needed.